Pengaruh Teknologi terhadap Kesadaran Manusia dalam Berfikir Filosofis - Hasbi Himatudin; Radea Yuli A Hambali (Gunung Djati Conference Series, 2023)
Technology has had a significant influence on the way humans think philosophically. On the one hand, technology can help in increasing a person's awareness of himself and his environment by providing tools that can help a person find out his health condition or provide information about the environment. However, on the other hand, technology can also affect concepts related to consciousness such as freedom, identity, and rationality, and has the potential to cause addiction which can reduce a person's ability to think critically and independently. This article uses a qualitative research method by focusing on studying related literature texts so as to find a conclusion on the problems above that, it is important for humans to understand and use technology wisely so they don't depend too much on technology and can use it in a balanced way.